Pengembangan E-Modul PELITA: Pembelajaran Lingkungan Untuk Indonesia Tangguh Berbasis Ekopedagogik Sebagai Upaya Menumbuhkan Ekoliterasi Peserta Didik - Wahyuni, Ajeng Restu; Sjaifuddin; Liska Berlian (UNIB Press, 2025)
The low level of students’ ecoliteracy and the limited use of relevant teaching materials in science subjects, particularly in environmental topics, serve as the background of this study. To address these issues, the E-Module PELITA: Pembelajaran Lingkungan Untuk Indonesia Tangguh, based on ecopedagogical approach was developed as an alternative solution to foster students’ ecoliteracy. The primary objective of this research was to examine the validity of the developed product and to assess students' responses toward the ecopedagogical-based E-Module PELITA as an effort to enhance ecoliteracy. This research employed the Research and Development (R&D) method by adapting the ADDIE development model, limited to three stages: Analyze, Design, and Development. Product validity testing was carried out through questionnaires administered to subject matter experts, media experts, and science teachers. Meanwhile, a small-scale trial was conducted to collect students’ responses through a questionnaire. The data were analyzed using both quantitative descriptive and qualitative approaches to provide insights into the feasibility and acceptance of the product. The findings revealed that the ecopedagogical-based E-Module PELITA achieved an overall validity level of 90.07%, categorized as “highly valid.” Specifically, assessments were provided by subject matter experts with an average score of 91.19%, media experts with 90.15%, and science teachers with 88.89%. In addition, students’ responses to the use of the module reached a score of 83.08%, categorized as “very well”.